Penerapan Metode Storytelling Berbasis Media E-picture Book untuk Meningkatkan Keterampilan Bercerita Imajinatif Siswa Kelas V Sekolah Dasar - Hermin Latifah Ismayanti; Linaria Arofatul Ilmi Uswatun Khasanah; Arfian Mudayan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Elementary school students' imaginative storytelling skills are still relatively low, characterized by a lack of vocabulary mastery, creativity/imagination in developing stories, and low self-confidence when speaking in front of the class. This study aims to improve imaginative storytelling skills of fifth grade students through the application of e-picture book media-based storytelling methods. The type of research used is classroom action research which was carried out in two cycles. The research subjects consisted of 22 students. Data collection techniques were carried out through observation and student performance tests. Data analysis used quantitative and qualitative descriptive techniques. Observation data were analyzed to determine the increase in teacher and student activity in the learning process, while performance test data were analyzed through calculating the average and percentage of completion levels. The results of the study were (1) teacher activity in cycle I was 67.5% to 90% in cycle II, increasing by 22.5%. (2) student activity in cycle I was 63.39% to 90.18% in cycle II, increasing by 26.79%. (3) Students' imaginative storytelling skills, which were initially 55% to 81.82%, experienced an increase of 26.82%. It can be concluded that the use of the e-picture book media-based storytelling method has a significant influence on learning activities, especially in improving imaginative storytelling skills in elementary schools, so it is suitable for use in learning.